Studenci wobec wyzwań współczesnego rynku pracy - przypadek województwa śląskiego = Students in the Face of Contemporary Labour Market - Silesia Province Case - Muster, Rafał (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the results of questionnaire studies performed on 986 students finishing first - and second - cycle studies in twenty two universities in Silesia province. The main objective of the studies was an attempt to answer the question how students see their chances to find a job, where and how they want to look for it and which skills or qualifications are, according to them, particularly desired by employers. Another aim of the research was to analyze the reasons for choosing university, area of study, virtual actions taken in case of becoming unemployed or even opinions on availability of guidance services. The research was co-financed with the resources of the European Social Fund.
Keywords: szkolnictwo wyższe; rynek pracy; studenci; województwo śląskie